Omsk state technical university as an innovative environment for the technical elite - A. . Kosykh (Высшее образование в России)
The article concerns the main trends of the scientific and educational activity of the university, its achievements for the recent years. The innovative structure of the university ischaracterized as a fundamental for the modern technical education. The article also presents the university development policy as the innovative centre of the Omsk region.